Evaluation of Independent Curriculum Implementation in Student-Centered Mathematics Learning at SMPN 1 Cikidang Sukabumi - Rosida, Rani Nurhayati; Prasetyono, Hendro (Yayasan Pendidikan Bima Berilmu, 2025)
The Independent Curriculum emphasizes student-centered learning; therefore, its implementation in Mathematics subjects at SMPN 1 Cikidang, Sukabumu needs to be evaluated. This study aims to examine how teachers design and implement Mathematics learning based on the Independent Curriculum and to reveal how students perceive its benefits and challenges. In addition, this research aims to assess the extent to which the implementation aligns with the core principles of the Independent Curriculum. The research employed a qualitative method with a field study approach, using in-depth interviews with teachers and students of SMPN 1 Cikidang. Data analysis was conducted descriptively through reduction, presentation, and conclusion drawing. The results show that teachers are fairly adaptive in designing contextual learning despite facing facility constraints, while students feel more motivated but require intensive guidance. The study concludes that teacher training and adequate facilities are essential to optimize Mathematics learning based on the Independent Curriculum.